Exploring Teachers' Needs for Technology-Based Learning in Elementary Education - Siti Istiqomah; Tri Murwaningsih; Sukarno Sukarno (Teknodika, 2025)
The integration of 21st-century skills, such as critical thinking, collaboration, and digital literacy, into elementary science education remains suboptimal. Preliminary observations in Purwantoro indicate that traditional teaching methods dominate, with limited use of interactive media, restricting the development of essential student competencies. This study addresses the need for innovative learning tools by exploring the potential of Smart Apps Creator (SAC) in enhancing IPAS (science and social studies) education. Employing a qualitative descriptive approach, data were gathered from five elementary school teachers through interviews, observations, and document analysis, meanwhile, the data analysis technique in this research uses descriptive analysis techniques. Findings reveal that SAC-based media effectively meet teachers’ needs by providing interactive features that promote engagement and independent learning. However, challenges such as limited infrastructure and teacher training were identified. The study underscores the significance of aligning educational practices with the demands of the digital era by integrating interactive media into the curriculum. It highlights the role of SAC in fostering 21st-century skills, offering practical recommendations for professional development and curriculum enhancement. It is hoped that the results of this research will have implications for innovative and technology-based learning as a step to accommodate learning in elementary schools more optimally.